Przestrzeń kulturowa i społeczna miasta jako problem badawczy - Irena Bukowska-Floreńska; Autor Autorowski (Studia Etnologiczne i Antropologiczne, 2016)
Mass migrations to industrial cities progressing with the development of different categories of industries in Polish cities, an extensive development of Silesian mines, steelworks and industrial production connected to them, made the rural people, coming here after the World War II with their own cultural baggage become labour workers, gain qualifications, take on and create new cultural patterns. The situation of the countryside so far investigated by the ethnologists was changing that is why the beginnings of the Polish ethnological studies on the cultural and social space of the city, already started in the 1960s, concern the observation of the process of its urbanization and history of rural people settling in cities. The researchers first started to observe the change of migrants; cultural patterns and the attitude of the city to ruralness and the other way round. They examined, above all, the culture of labour communities which absorbed the groups of newcomers or held their own folk industrial culture created in the course of the development of urban tecgnical civilization. Such stud¬ies were conducted in Upper Silesia, Lodz, Zyrardów, Warsaw, Konin and other cities. With time, the studies on the cultural and social problems of the cities spread, deepen and specify. What caused that constituted, above all, the studies conducted in Lodz, where the researchers aimed at defining the subject and methodological assumptions of the studies on big city commu¬nity. As a result, the knowledge on the cultural tradition of labourers from Lodz and their families was collected. Hierarchies of values, social life in a given space of living (a tenement), which is an intermediary space for man, between a social wide and the place of his/her own existence. The cities and suburban areas, with a created cultural specificity, were dealt with by Silesian researchers who extended the very subject matter by the notions within the scope of the ecology of culture. The proc¬esses of cultural adaptation to the conditions formed in the former rural environment, in villages around industrial factories, determined here not only the subject matter, but also a research strategy, going beyond the method of a monographic and integrative description traditional for ethnologists. Thus, remaining it initially, it was gradually enriched by a multiaspectual and diagnostic way of inquir¬ies, allowing for not only getting to know the origins of the reality examined and its classification, but also its importance for the existence and needs of the city community, for shaping the way and life style, social norms, for the system of values, mechanisms of the functioning of the contemporary city.